Chronic atrazine exposure increases the expression of genes associated with GABAergic and glutamatergic systems in the brain of male albino rat - Reyes-Bravo, D. Y.; Villalobos-Aguilera, P.; Almonte-Zepeda, J. T.; Mendoza-Trejo, M. S.; Giordano, M.; Orozco, A.; Rodríguez, V. M. (Frontiers in Toxicology, 2022)
The herbicide atrazine (ATR; 2-chloro-4-ethylamino-6-isopropylamino-s-triazine) is widely used to destroy grasses and broadleaf weeds in crops and some fruits. Studies in rodents have shown that acute, repeated or chronic exposure to ATR is associated with alterations in the nigrostriatal dopaminergic pathway, whereas its effects on GABAergic and glutamatergic pathways have only recently been reported. Sprague-Dawley male rats were exposed daily to 1 or 10 mg ATR/kg of BW for 13 months to evaluate the ATR effects on GABAergic and glutamatergic systems. At the end of the ATR treatment, the levels of mRNA of several genes involved in the production, vesiculation, reuptake, and receptors of GABA and Glu in the striatum (STR), nucleus accumbens (NAcc), prefrontal cortex (PFC), ventral midbrain (vMID) and hippocampus (HIPP) were evaluated by absolute qPCR. For the GABAergic genes, increased expression of GAD67 and Slc32a1 in STR and/or vMID in rats exposed to 1 and/or 10 mg ATR were detected. With regard to the expression of genes involved in the glutamatergic system, Slc17a6 and Grin1 in HIPP of rats exposed to 1 and/or 10 mg ATR, increased as was Gria1 in STR and PFC in the group exposed to 1 mg ATR. In the same fashion, Slc1a3 expression and MGLUR1 increased in STR of rats exposed to 1 and 10 mg ATR groups. The expression of the glutaminases gls (variants 1 and 2) was greater in STR, NAcc, HIPP, and PFC of rats exposed to 1 and/or 10 mg ATR. These findings show that the GABAergic and, especially glutamatergic systems are targets of ATR exposure.